Simply crochet : 22 stylish designs for everyday - Chachula, Robyn, 1978- (Interweave Press, 2011)
"In general crocheters tend to be much more budget conscious than knitters. We see this in their preferences for less expensive big box yarns, small projects, and practical projects for home dčor and gifts. So this book will marry the crafter on a budget to great crochet designs which has yet to be done successfully in competitive titles. It will show that just because you are on a budget it does not mean you cannot make fabulous crochet projects. Techniques in the book will be geared for the advanced beginner, but the projects will appeal to crocheters of every skill level. Simply Crochet will help crocheters get the most enjoyment out of just a few balls of yarn. It will answer questions like: "What can I make with this one beautiful ball of yarn? Can I really make shawl with only 3 balls of yarn? Can I make something with scraps from a few old projects?" The book will center around 30 projects that use 5 balls or less of yarn, divided into sections by the amount of yarn, namely 1, 3, and 5 balls. The 1 skein section will concentrate on accessories like jewelry, scarves, and bags. In the 3 skein section, the reader will find shawls, socks, home, and baby items. The final section of 5 skeins or less, will have garments such as vests, skirts, cardigans, and jackets, and larger home items. Scattered throughout the sections will be helpful tips on making your yarn stash last such as how to choose the right stitch or stitch pattern to make your ball go the furthest; ideas on how to use leftover balls of yarn in new ways; and how to recycle an old project or sweater for its yarn"--